2021
DOI: 10.1111/cdep.12404
|View full text |Cite
|
Sign up to set email alerts
|

Studying Peers in Research on Social Withdrawal: Why Broader Assessments of Peers are Needed

Abstract: It has long been assumed that children and adolescents want to be with their peers and therefore make active efforts to engage with them. However, a sizable minority of youth avoid peers for internal reasons (e.g., anxiety, preferences for solitude) or because they are socially withdrawn. Although by definition, withdrawn youth tend to stay away from peers, they do interact and form relationships with peers. Yet most research assesses peers narrowly, focusing almost exclusively on youth who share the same gend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 38 publications
(56 reference statements)
0
11
0
2
Order By: Relevance
“…For instance, higher security in peer attachment intervenes on the negative effect of parental attachment insecurity on teenagers’ depressive symptoms, particularly in girls [ 29 , 51 ]. Other authors [ 5 , 52 ] reported that teenagers who are insecurely attached to their parents but securely attached to their peers show better adjustment and fewer symptoms [ 5 , 42 , 43 , 44 , 52 , 53 ].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, higher security in peer attachment intervenes on the negative effect of parental attachment insecurity on teenagers’ depressive symptoms, particularly in girls [ 29 , 51 ]. Other authors [ 5 , 52 ] reported that teenagers who are insecurely attached to their parents but securely attached to their peers show better adjustment and fewer symptoms [ 5 , 42 , 43 , 44 , 52 , 53 ].…”
Section: Introductionmentioning
confidence: 99%
“…Social withdrawal refers to the behavioral tendency to withdraw from and avoid familiar and unfamiliar peers (Rubin et al, 2009). Although its concurrent and predictive psychological risks across the lifespan are now well-established, so too is the heterogeneity in the negative psychological outcomes of social withdrawal (Bowker et al, 2012;Bowker & White, 2021). Put simply, not all individuals who regularly withdraw from their peers suffer significantly.…”
mentioning
confidence: 99%
“…It seems that building cross-sex peer relations can be particularly useful for gay adolescents since it is known that heterosexual girls tend to express less prejudice than heterosexual boys towards gay boys, and thus, cross-sex friendship may provide for gay adolescents an opportunity to establish a larger social support network [ 116 ]. Further to this, Bowker and White [ 117 ] also draw attention to the psychological benefits of other-sex relations for withdrawn boys, “because their behaviors may be more consistent with gender norms for girls, especially during middle childhood and early adolescence when gender norms tend to become more flexible” [ 117 ].…”
Section: Discussionmentioning
confidence: 99%